Obstetric perinatal outcomes in COVID-19-positive pregnant women - Begum, Kazi Nazma; Akther, Farjana; Bushra, Sumaiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: In December 2019, a novel coronavirus disease (COVID-19) emerged in Wuhan, China, with an incredible infection rate. The vertical transmission of COVID-19 is uncertain. Pregnant females are considered a high‑risk group for the prevention and control of various communicable diseases. This study aimed to assess the obstetric perinatal outcomes in Covid-19 positive pregnant women. Methods: This was a descriptive cross-sectional study and was conducted in the department of Obstetrics and Gynaecology, Mugda Medical College, Dhaka, Bangladesh from 26 March 2021 to 21 July 2022. A total of 94 pregnant women diagnosed as COVID-19 patients by RT-PCR tests were enrolled in this study as the study subjects purposively. Data were analysed by using MS Office tools. Results: In the study, 23% of participants experienced lower abdominal pain as a pregnancy symptom, with 11%, 4%, and 9% reporting premature rupture of membranes, decreased fetal movement, and antepartum haemorrhage, respectively. Among the participants, 45% had vaginal deliveries, 15% had assisted vaginal deliveries, and 40% underwent lower uterine caesarean sections. Notably, 11% required ICU admission. The study recorded maternal and neonatal mortality rates of 2% and 4%, respectively, and 9% of babies needed incubation. The average APGAR score (5 minutes) was 6.8±0.2, and the mean birth weight was 2.5±0.3. Conclusions: Lower abdominal pain and premature rupture of membranes (PROM) may be considered some major pregnancy symptoms for COVID-19-positive pregnant women. For such cases, proper facilities for LUCS, ICU and incubation are needed.